Educational Practices for a New Nigeria: An Exploratory Study - Aydin, Hasan; Lafer, Stephen (Alberta Journal of Educational Research, 2016)
This article reports on a qualitative study conducted at the Nigerian Turkish International Colleges (NTICs) in Abuja, Nigeria. Twenty-two participants comprised of three administrators, seven teachers, four parents, and eight students participated in the study. The data collected through observations, informal, formal and semi-structured in-depth individual interviews, focus groups, document analysis (of teachers’ syllabi, coursework materials, Nigerian nation-wide exam reports, and copies of district and state lesson design guidelines), and field notes were used for content analysis. Themes of the study were constructed to explore the schools’ role in promoting openness, mutual understanding, and habits of discourse vital to democracy in a society that is deeply divided along religious, ethnic, and geographical lines. This article explains the value of NTICs by focusing on the role of curriculum in promoting tolerance, unity, economic prosperity, and stability. This article also considers how these NTICs attempt to encourage the establishment of a civil society based upon democratic principles of governance while focusing on multicultural values. Cet article présente les résultats d’une étude entreprise aux Nigerian Turkish International Colleges (NTICs) à Abuja, au Nigeria. L’étude a impliqué 22 participants, dont trois administrateurs, sept enseignants, quatre parents et huit étudiants. Les données ont été recueillies lors de séances d’observation, d’entrevues individuelles approfondies (informelles, formelles et semi-structurées), de groupes de discussion, d’analyse documentaire (plans de cours des professeurs, matériel de cours, rapports portant sur des examens à l’échelle du Nigeria, lignes directrices de la part des districts et de l’état pour la conception des cours) et par des notes prises sur le terrain. Les thèmes élaborés pour l’étude visaient l’exploration du rôle de l’école dans la promotion de l’ouverture, la compréhension mutuelle et les habitudes de discours essentielles à la démocratie dans une société qui est profondément divisée selon des clivages religieux, ethniques et géographiques. Cet article explique la valeur des NTICs en se penchant sur le rôle des programmes d’études dans la promotion de la tolérance, l’unité, la prospérité économique et la stabilité. De plus, il considère les efforts de ces NTICs pour encourager l’établissement d’une société civile reposant sur des principes démocratiques de gouvernance tout en tenant compte de valeurs multiculturelles.